2007
DOI: 10.1111/j.1439-0531.2006.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Weight, Age and Breeding History on Canine Sperm Quality Parameters Measured by the Hamilton‐Thorne Analyser

Abstract: During the last decade, several computer assisted sperm analysis (CASA) systems have been validated for canine sperm quality assessment. Regarding the impressive possibilities of these systems, further research is required to determine which CASA measurements are of clinical importance in canine andrology. In the present study, the sperm quality parameters obtained by the Hamilton-Thorne Semen Analyser (Ceros 12.1; HTR) were correlated with the body weight and the age of the dogs. Moreover, the sperm quality p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 26 publications
6
57
2
4
Order By: Relevance
“…In the infertile dogs, sperm concentration, percentage of spermatozoa with normal morphology, and the majority of most of the evaluated motility parameters were significantly (P < 0.05) lower than in fertile dogs. The results were in agreement with those reported by Rijselaere et al (20) and Niżański et al (16). They have found, that almost all of the evaluated sperm characteristics was significantly poorer in dogs with lower fertility.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the infertile dogs, sperm concentration, percentage of spermatozoa with normal morphology, and the majority of most of the evaluated motility parameters were significantly (P < 0.05) lower than in fertile dogs. The results were in agreement with those reported by Rijselaere et al (20) and Niżański et al (16). They have found, that almost all of the evaluated sperm characteristics was significantly poorer in dogs with lower fertility.…”
Section: Discussionsupporting
confidence: 93%
“…However, there are only few studies on the relationship between sperm characteristics assessed by CASA and fertility in dogs. Rijsselaere et al (20), and Niżański et al (16) have found significant differences between fertile and subfertile dogs in most of the sperm parameters assessed by CASA. Thus, the aim of the study was to evaluate semen quality parameters in infertile dogs by the Hamilton-Thorne Semen Analyser.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Possible fluctuations in seminal quality are associated with factors such as breed (Rijsselaere et al, 2007), age (Stone et al, 2013), seasonality (Chemineau et al, 2008;Zhang et al, 2013), temperature (Thonneau et al, 1998), photoperiod (Mazzarri et al, 1970;Kozdrowski and Dubiel, 2004), and other factors of different etiology. All of these factors require careful control to attain the best semen quality for artificial insemination.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining motility parameters evaluated in the CASA system are difficult to interpret. According to the literature, motility parameters, excluding BCF, LIN and STR, are significantly correlated with fertility in dogs (Rijsselaere et al 2007). The threshold values of VAP, VSL and VCL, which are indicative of low and high levels of fertility in dogs, have not yet been clearly defined.…”
Section: Discussionmentioning
confidence: 99%